Indices employed for the assessment of "urban outdoor ventilation" - A review. (15th February 2020) - Peng, Yunlong; Buccolieri, Riccardo; Gao, Zhi; Ding, Wowo
Abstract: In recent years, several ventilation indices have been proposed and applied to assess the efficiency of "urban outdoor ventilation", i.e. the ability of an urban area to dilute pollutants, heat and moisture by exchanging air between inside and above of the urban canopy. Here, focusing on the pollutant dispersion, the definition of 13 ventilation indices is given, which includes indoor-initially proposed and outdoor directly proposed. Then, 63 literature studies (published until 2018) applying the ventilation indices are selected, analysed and summarized in terms of the types of geometry investigated, the timeline and the frequency of employment of each index, the turbulence models employed. Based on the analysis of such studies, advantages and limitations of each index are provided, which may help the scientific community to choose the most appropriate one depending on the specific application and objective. Future perspectives are also given, suggesting the necessity to correlate ventilation indices with urban morphological parameters, to apply indices in real urban areas characterized by building height variability and complex morphology, as well as to provide threshold values useful for urban planning purposes. Graphical abstract: Image 1 Highlights: Main ventilation indices employed for urban outdoor ventilation are summarized. A review of 63 studies employing 13 ventilation indices is performed. Advantages and limitations of each index are provided. Suggestions on the use of indices for urban geometries are given.